2014
DOI: 10.1590/s0036-46652014000400010
|View full text |Cite
|
Sign up to set email alerts
|

INCIDENCE OF DIARRHEA BY Clostridium difficile IN HEMATOLOGIC PATIENTS AND HEMATOPOIETIC STEM CELL TRANSPLANTATION PATIENTS: RISK FACTORS FOR SEVERE FORMS AND DEATH

Abstract: We describe the rate of incidence of Clostridium difficile-associated diarrhea (CDAD) in hematologic and patients undergone stem cell transplant (HSCT) at HC-FMUSP, from January 2007 to June 2011, using two denominators 1,000 patient and 1,000 days of neutropenia and the risk factors associated with the severe form of the disease and death. The ELISA method (Ridascreen-Biopharm, Germany) for the detections of toxins A/B was used to identify C. difficile. A multivariate analysis was performed to evaluate potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
5
18
1
1
Order By: Relevance
“…In particular, a severe form of CDI developed in 23% of allogeneic HSCT recipients, and all of them died. 88 Of note, 89% of patients in this cohort received initial treatment with metronidazole that might have influenced the clinical course of CDI.…”
Section: Clostridium Difficile Infectionmentioning
confidence: 96%
“…In particular, a severe form of CDI developed in 23% of allogeneic HSCT recipients, and all of them died. 88 Of note, 89% of patients in this cohort received initial treatment with metronidazole that might have influenced the clinical course of CDI.…”
Section: Clostridium Difficile Infectionmentioning
confidence: 96%
“…Over the past decade, CDI has increased in both frequency and severity in the USA and in other countries [ 7 9 ]. CDI has reportedly been widely identified in prospective laboratory surveillance and outbreaks [ 10 13 ]; however, there are few reports on the frequency and impact of CDI in different institutions, especially in Latin America. Accordingly, we performed the present study to determine factors associated with C. difficile infection among patients with hospital-acquired diarrhea and with poor prognosis among those with documented C. difficile colitis in a tertiary care Brazilian hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 550 patients who underwent HCST during the study period, 6% (35/550 patients) subsequently developed CDI. Within the literature, the incidence of CDI after all HSCT ranges from 3–17% . A higher incidence of CDI is reported among patients who underwent allogeneic HSCT .…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature, the incidence of CDI after all HSCT ranges from 3-17%. 8,[19][20][21][22][23] A higher incidence of CDI is reported among patients who underwent allogeneic HSCT. 19,24,25 In our study, we also found that most patients who underwent HSCT and who developed CDI had undergone an allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%